Young people's climate activism: A review of the literature - Neas, Sally; Ward, Ann; Bowman, Benjamin (Frontiers in Political Science, 2022)
The year 2018 was a watershed year for young people's climate activism. In this review article, we explore the methodological trends and key themes across contemporary academic literature on young people's climate activism. In the academic literature, following an initial wave of survey-based research of young people and textual analysis of secondary data like media reportage, the field is experiencing a second wave of qualitative research and a resurgence of emphasis on youth voice in research. Accordingly, we identify the strengths of the existing literature in its exploration of key themes including the composition, practices and outcomes of young people's climate activism, and the ways young people understand and act on climate change. We identify several gaps in the literature that arise from a disproportionate focus on research topics, and especially a disproportionate focus on activism in the global North and in wealthy and White communities, a focus on mass mobilizations, and an intensive interest in the individual activist Greta Thunberg. Our analysis leads to recommendations for future research based on three conceptual challenges. We argue that future research must respond to these challenges: first, the limited and constraining social constructions of “youth” as a category; second, the practical challenges of working with young people, not least in relationships of consent; and third, the need to respond to adultism in research practices and to develop youth-centered approaches to the activism of young people. This review article intends to contribute to a step change in theory and methods for the study of young people's climate activism.